Hematological Findings among COVID-19 Patients Attending King Khalid Hospital at Najran, Kingdom of Saudi Arabia - Elkhalifa, Ahmed M. E.; Elderdery, Abozer Y.; Al Bataj, Ibrahim Ali; Tamomh, Abdelhakam G.; Alyami, Masaud M.; Almakrami, Hussein A.; Alofair, Mubarak A.; Almorish, Mohammed A.; Bashanfer, Salem; Tabash, Mohammed I.; Idris, Hadeil M. E.; Ahmed, Dania Z.; et al. (BioMed research international, 2022)
COVID-19 is a global pandemic viral infection that has affected millions worldwide. Limited data is available on the effect of COVID-19 on hematological parameters in Saudi Arabia. This study is aimed at examining the role of hematological parameters among COVID-19 patients admitted to King Khalid Hospital in Najran, Saudi Arabia. This is a retrospective, hospital-based study of 514 cases who were recruited during August to October 2020. 257 COVID-19 patients formed the study group, and a further 257 negative subjects formed the control group. Anemia was significantly elevated in positive subjects over controls (respectively, 64.2% and 35.8%), with patients 2.5 times more likely to be anemic (p<0.01). Thrombocytopenia was higher in patients over controls (respectively, 62% and 38%), with patients ~1.7 times more likely to be thrombocytopenic (p<0.01). Moreover, leukopenia was significantly higher in patients over controls (respectively, 71% and 29%), with positive subjects ~2.6 times more likely to be leukopenic. Our study results indicate that mild anemia associated with leukopenia may have diagnostic value for COVID-19. Careful assessment of hematological parameters, at baseline and throughout the disease path, will assist physicians in formulating personalized approaches to treatment and promptly offer intensive care to those in greater need.